Bronchial carcinoid in children - Aneeshkumar, Surendran; Sundararajan, L.; Sunder, T.; Shahnaz, Ayesha (International Journal of Research in Medical Sciences, 2018)
Bronchial carcinoids (BCs) are uncommon, slow growing, low-grade malignant neoplasm comprising 0.5-2.5% of all primary lung cancers. Although BC’s in childhood often have an endobronchial location causing airway obstruction, they are frequently misdiagnosed as benign conditions, resulting in a delay in definitive diagnosis and treatment. Lung sparing surgery should be done whenever possible, more so in children, for better quality of life and minimizing skeletal abnormality which follows pneumonectomy. We present two cases of bronchial carcinoid in young children.